Case Study on the Use of Internationalisms by Graduated Translators and Students of Translation and Interpreting Studies - Sazdovska Pigulovska, Milena (Faculty of Education, University “St. Kliment Ohridski”– Bitola, 2015)
Global developments often affect the language people use in order to express contemporary processes and novelties. The Macedonian language is not immune to the inflow of new international terminology, which is strongly evident in both oral and spoken form. This tendency is also observed among graduate translators as well as among students at the Faculty of Philology in Skopje attending translation and interpreting studies who face the growing challenge of using international vocabulary as opposed to domestic equivalents. The main purpose of this case study is to examine their tendency for use of international lexis as opposed to domestic lexis in the translations of specialised political and economic texts as well as to inquire into the reasons for such use. Moreover, the ultimate goal of this case study is to draw adequate conclusions in the relevant subject-matter, which will also produce statistically analysable data on the basis of which applicable solutions can be proposed for the current and future students at the Department of Translation and Interpreting.
Keywords: International terminology, domestic lexis, specialised translation, survey